2013
DOI: 10.1007/s11832-013-0529-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of distal humeral fractures and surgical treatment in 0- to 18-year-old patients treated in Finland from 1987 to 2010

Abstract: Background Studies of pediatric and adolescent fractures in general report a significant increase in the incidence of upper-extremity fractures as well as in their surgical treatment. The aim of this study was to determine the trends of the incidence and treatment of distal humeral fractures in hospitalized 0-to 18-year-old patients in Finland. Method The study included the entire pediatric and adolescent (\19 years) population in Finland during the 24-year period from 1 January 1987 to 31 December 2010. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…13 A similar increase (30%) of distal humerus fractures was found in patients who were hospitalized between 1987 and 2010 in Tampere, Finland. 21 An increasing trend of supracondylar humerus fractures has been reported in many other developed countries, together with other upper extremity fractures. 16 The increase in incidence may be explained by changes in children's activity patterns.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 A similar increase (30%) of distal humerus fractures was found in patients who were hospitalized between 1987 and 2010 in Tampere, Finland. 21 An increasing trend of supracondylar humerus fractures has been reported in many other developed countries, together with other upper extremity fractures. 16 The increase in incidence may be explained by changes in children's activity patterns.…”
Section: Discussionmentioning
confidence: 98%
“…19,20 Their in-hospital treatment has increased throughout 1987 to 2010, according to hospital discharge registries. 21 However, the current epidemiology of supracondylar humerus fractures is still poorly understood 22 and population-based studies are scarce. 23 Correspondingly, the recent incidence of pediatric supracondylar humerus fracture at population level is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Such a high rate of fixation failure would be alarming in any fracture or patient group. The issue is particularly important in children population, while the incidence of supracondylar fractures has increased by 30% since 2000 (27), and their in-hospital treatment is increasing (28). Nevertheless, the poor stability found in this study was not surprising; lateral-only pinning has been reported to be 40% weaker biomechanically when compared with crossing medial and lateral pinning (19).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of longterm morbidity is more than 40% in flexion-type supracondylar humerus fractures [17]. Further, the incidence and surgical treatment of supracondylar humerus fractures are increasing [13,26,29], resulting that any preventive interventions are justified to decrease these injuries. In order for preventative action to be effective, biological, environmental and behavioral background factors need to be understood.…”
Section: Discussionmentioning
confidence: 99%